Gabapentin and oral antidepressants for chronic pruritus: a prospective cohort study evaluating efficacy and side effects in daily dermatological practice - T. A. Kouwenhoven; P. C. M. van de Kerkhof; M. Kamsteeg (Taylor & Francis Group, 2023)
AbstractBackground Chronic pruritus is frequently seen in daily dermatological practice and is associated with marked impact on quality of life. Research on the use of gabapentin and oral antidepressants in daily dermatological practice is scarce.Objective To evaluate the efficacy and safety of gabapentin and oral antidepressants in patients with chronic pruritus in daily clinical practice.Methods A prospective observational single-center cohort study was conducted including adult patients with chronic pruritus and an indication for systemic treatment between June 2016 and May 2019.Results Systemic treatment with gabapentin and/or antidepressants was initiated in 31 patients with severe chronic pruritus (median average pruritus NRS score 7.0), in which most cases no underlying origin was identified (83.9%). In patients treated with gabapentin 900-1800 mg/day (N = 25), median average pruritus NRS decreased to 5.5 (IQR 3.0) after 4 weeks and remained stable up to 24 weeks of treatment. Efficacy of antidepressants was variable, with the highest response after initiation of amitriptyline, nortriptyline, and mirtazapine. Side effects were frequently observed in both gabapentin and antidepressant treatments; however, were mostly mild and temporary.Limitations This was a single-site observational study, with limited sample size.Conclusion Treatment with gabapentin and antidepressants should be considered in patients with chronic pruritus unresponsive to conventional treatment.